SYNTHESIS AND CHARACTERIZATION OF AN AZO DYE AND ITS IRON COMPLEX - Myek, Bako; Sunday, Nathan; Agbamu, Ochigbo Festus (FUDMA JOURNAL OF SCIENCES, 2022)
An azo dye and its iron complex have been synthesized and characterized using IR and UV-Vis spectrophotometer. The azo dye is prepared by coupling 3-aminophenol and 2-naphtol after which the iron complex is synthesized by coupling the unmetallised dye with FeCl3. The unmetallized dye has its maximum absorption wavelength at 436.00nm while the metal complex dye has 341.50nm. The IR spectra showed the value of â€“N=N- stretching frequency at 1458.23cm-1 for both the unmetallised dye and its metal complex, and which is within the range of 1400-1500cm-1. This indicates that the synthesized complexes contain azo an azo group. The IR spectra showed the value of C-N frequency at 1267.27cm-1 for both the unmetallised dye and its metal complex. Also, The IR spectra showed the value of O-H frequency at 3408.33cm-1 for dye while 3402.54cm-1 for metal complex dye. C=C has the IR spectra frequency of the dye at 1514.17 cm-1Âwhich is within the range of 1450-1600 cm-1. The metal complex dye shows the IR value of Fe-N at 263 cm-1 and Fe-O at 576 cm-1
Keywords: 3-aminophenol, 2-naphhtol, Unmetallized dye, Complex, UV-Vis